2011
DOI: 10.1111/j.1442-9071.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability to determine postoperative status of macular hole in gas-filled eyes by spectral-domain optical coherence tomography

Abstract: The status of a macular hole can be determined by spectral-domain optical coherence tomography on postoperative day 1 even in gas-filled eyes. The visibility depends on the volume of intravitreal gas and the absence of a posterior staphyloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…It is very difficult to compare the imaging success rate of the present study with those of the other studies that used SD-OCT (i.e., Eckardt et al [8] , Masuyama et al [9] , Sano et al [13] and Goto et al [14] ), however, because of the small sample size of these five studies. Postoperative face-down positioning, however, leads to the accumulation of a considerable amount of keratic precipitates in the central cornea, which could affect the coherence of the measuring light.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…It is very difficult to compare the imaging success rate of the present study with those of the other studies that used SD-OCT (i.e., Eckardt et al [8] , Masuyama et al [9] , Sano et al [13] and Goto et al [14] ), however, because of the small sample size of these five studies. Postoperative face-down positioning, however, leads to the accumulation of a considerable amount of keratic precipitates in the central cornea, which could affect the coherence of the measuring light.…”
Section: Discussioncontrasting
confidence: 49%
“…They reported that imaging was possible for 25 of 33 eyes (75.8%) at 24 hours after surgery, for 29 eyes (87.9%) at 48 hours after surgery, and all eyes at POD 3 using an air tamponade. Masuyama et al [9] reported that imaging was possible using 16% SF6 gas as the tamponade for 3 of 5 eyes (60.0%) at 3 hours after surgery, and for 13 of 16 eyes (81.3%) on POD 1 and 2 by SD-OCT. Sano et al [13] reported that the postoperative status of the MH could be determined in 24 of 26 eyes (92%) on POD 1 by SD-OCT. Goto et al [14] reported imaging success rate was 22 of 25 eyes (88.0%) on POD 1 and 23 of 24 eyes (95.8%) on POD 2 by SD-OCT. Hasler and Prunte [15] were able to evaluate the macula by TD-OCT during the immediate postoperative period, and determined that the MH was closed in two eyes half-filled with air on POD 1 and the MH was closed in 28 of 30 eyes (93.3%) while in 2 eyes (6.7%) the MH was not closed on POD 3, based on images obtained with the measuring beam passing through the vitreous humor. When the beam passed through gas-filled eyes, however, a clear image could not be obtained because of a strong light reflection from the posterior surface of the gas.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports of SD-OCT for gas-filled eyes including ours, the quality of images was apparently poorer than the present results and most of them seemed to be SS 4 or less on the present scale [16,17,18]. Sano et al [19] presented comparatively clear images of 2 eyes with gas, which are likely to be SS 6 images; however, neither the quality of images nor sensitivity of any cases were described in their article. In the present study, the sensitivity needed to obtain a clear image to identify the MH (SS ≥4) was 100%, and to identify the IS/OS line (SS ≥6) the sensitivity was 70%, which is much better than the previous results.…”
Section: Discussioncontrasting
confidence: 39%
“…There are several reports of SD-OCT being used to determine closure of MH in gas-filled eyes after surgery, where the inner surface of the retina and MH closure were identifiable. However, the ability to determine MH closure was about 80%, less than or comparable to 92% [16,17,18,19]. Furthermore, the quality of images was not mentioned or lacked clarity, and the structure of the sensory retina could not be observed clearly.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the earliest successful imaging of MH status in gas-filled eyes was on the day following the operation (>24 h) using SD-OCT [3,11,12,13,14,15,16,17]. In the present study, the very early dynamics of MH closure were investigated in gas-filled eyes using SS-OCT starting from approximately 20 min after vitrectomy.…”
Section: Introductionmentioning
confidence: 99%